Protection of the Self-Employed to the Extent of Non-Discrimination and Equal Treatment – An Overview of the Issue - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The subject of the foregoing study is the analysis of the legal regulation of the protection of the self-employed to the extent of non-discrimination and equal treatment. The author positively assesses the very fact of adopting the Equality Act, which contributed to raising the standards of protection of self-employed people in this area. Unfortunately, however, a number of detailed regulations included in this act raise justified doubts and deserve criticism. Moreover, some provisions of the Equality Act are inconsistent with international agreements binding Poland, and also violate Art. 32 of the Constitution of the Republic of Poland. This leads to an unjustified lowering of the standards of protection against discrimination and unequal treatment of the self-employed in relation to the legal situation in which employees find themselves. A critical analysis of the Equality Act shows the far-reaching inconsistency of the legislator and the inconsistency of the entire system of protection against discrimination. This, in turn, makes this law ineffective, as shown by statistics in which a very small number of cases are brought to court and end up with a positive outcome for the person discriminated against.